GAMBARAN PASIEN VARIKOKEL KIRI YANG MENJALANI OPERASI PALOMO PROCEDURE DI RUMAH SAKIT PEKANBARU MEDICAL CENTER PERIODE JANUARI 2009 – DESEMBER 2013 - Nia Mustika; Zuhirman "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Palomo Procedure operation is one of a selection therapy used for therapy of varicocele. This is caused this operation easier to performed and the costs more affordable. This research aims to gain an overview of patients with left varicocele undorge Palomo Procedure operation in Pekanbaru Medical Center hospital from January 2009 – December 2013. This research is descriptive retrospective research. The datas used in this research are the 152 datas from patients with varicocele’s medical records. The results of this research indicate that all incidence of left varicocele found in range 16 – 20 years old and bilateral varicocele found in range 41 – 45 years old. Left varicocele grade 2 (40,13%), varicocele grade 3 (59,21%), and bilateral varicocele grade 3 (0,66%). Palomo Procedure is done with indication of varicocele grade 2 and 3 and in terms of a job (99,34%) and by indication of bilateral varicocele (0,66%). Complications of this operation are wound dehiscence (3,29%), wound dehiscence and hydrocele (0,66%). The conclusions from the results of this research are all left varicocele incidence found in range 16 – 20 years old and bilateral varicocele in range 41 – 45 years old, most in the grade 3. Palomo procedure most performed with indications of varicocele grade 2 and 3 also in terms to a job with most complication is wound dehiscence.Keyword : Palomo Procedure, left varicocele